Endonasal Septal Perforation Repair Using an Interpositional Porcine Dermal Collagen Implant. (2nd September 2014) - Amin, Nikul; Syed, Irfan; Hunter, Benjamin; Roberts, David N.
Abstract : Objectives: Describe our novel minimally invasive technique for closure of nasal septal perforations. Methods: We describe our experience in a series of patients from 2 London teaching hospitals treated using the same surgical technique. Closure of the defect was undertaken using one inferiorly based nasal floor mucosal flap and a contra‐lateral superiorly based vascularized septal mucosal flap. This was achieved by a closed endonasal approach with a porcine dermal collagen sheet interpositional graft (Permacol) placed on the more concave side of the perforation. The mucosal flaps are used to cover the repair and sutured in place. Results: Septal perforations of up to 2‐cm diameter were successfully repaired in greater than 90% of cases over a 36‐month follow‐up period. Conclusions: Our novel technique has proved effective in closure of septal perforations. Permacol is a durable graft, utilizing acellular cross‐linked collagen matrix, used commonly in abdominal hernia repair. We found Permacol to be a biocompatible graft with the ability to resist dessication if there is slow re‐epithelization or partial exposure, making it a robust and easy to use interpositional graft with no morbidity from graft harvesting. The use of local intranasal mucosal advancement flaps allows a minimally invasive approach without any external incisions or scars. Potential limitations are the size of the pedicled flaps for very large perforations, or the lengths of the flaps for very anterior defects. For the majority of septal perforations the authors feel this technique offers an effective minimally invasive option with low morbidity.